Oxygen-sensitive T2* magnetic resonance imaging to correlate heart function and ischemic etiology of post-hospitalized chronic heart failure patients. Issue 128 (July 2020) - Juan, Yu-Hsiang; Huang, Pei-Ching; Lin, Gigin; Liu, Min-Hui; Lin, Yu-Ching; Wang, Jiun-Jie; Ng, Koon-Kwan; Cheung, Yun-Chung; Wang, Chao-Hung; Ng, Shu-Hang
Highlights: T2* values positively correlated with left heart function in heart failure patients. T2* values differ between ischemic and non-ischemic cause of chronic heart failure. Both ischemic and non-ischemic heart failure groups showed reduction of myocardial oxygenation. Ischemic and reduced ejection fraction subgroup showed lowest myocardial oxygenation. Abstract: Purpose: Myocardial oxygenation imaging is a field-of-interest but its clinical utility largely unexplored. We aimed to investigate the myocardial oxygenation status via T2* imaging and compared with the left ventricular ejection fraction (LVEF) in chronic heart failure (HF) patients after hospitalization. Also, we sought to compare the differences in myocardial oxygenation status among patients with ischemic HF, non-ischemic HF and controls. Methods: We prospectively enrolled 60 participants, comprising 20 HF patients with LVEF ≥ 50 % as the improved ejection fraction (HFIEF) group, 20 H F patients with ejection fraction <50 % as the reduced ejection fraction (HFREF) group, and 20 controls. Patients were also dichotomized into ischemic and non-ischemic subgroups. T2* values were compared across the study groups, and correlated with LVEF, myocardial scar distribution and quantity. Results: T2* values positively correlated with LVEF and were significantly lower in the HFREF group as compared with both HFIEF and controls (20.06 vs. 24.23; 20.06 vs. 26.32, respectively, both p < 0.05). Lower T2* values were observed in the HFREF group than the HFIEF group and the ischemic subgroup than the non-ischemic subgroup. No significant correlation existed between T2* value and the myocardial scar amounts in ischemic territory. Conclusions: Oxygen-sensitive T2* measurements showed correlation with LVEF and ischemic etiology in chronic heart failure patients, while the ischemic HFREF patients appeared to be more vulnerable to myocardial oxygen reduction than other groups. T2* measurements may be clinically feasible in monitoring heart failure via myocardial oxygenation and lay the foundation for future studies in prediction heart failure recovery.